Statistical Variance and Transpositional Analysis: A Commentary on Plazak (2016) - Shaffer, Kris (Empirical Musicology Review, 2016)
Joseph Plazak argues for a more nuanced representation of the environment in which listeners encounter music ― in particular, questioning the assumption that listeners who engage with music repeatedly do so at the same absolute pitch level. While I agree with Plazak's problematization of this assumption, as well as his advocacy of further investigation into it, Plazak's corpus study has two key methodological flaws. However, a follow-up study in line with Plazak's research could both address these flaws and the more general question that Plazak raises, to the benefit of our understanding of a number of foundational cognitive issues.